Increasing Employee Loyalty through Career Development and Engagement: The Mediating Role of Job Satisfaction in Five-Star Hotels in Greater Jakarta - Soerjanto; Sulistyo Haryono; Sulih Wahyudiono (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Employee loyalty remains a critical challenge in the hospitality industry, where high work pressure and dynamic service demands often lead to high employee turnover. Although career development and employee engagement have been widely recognized as drivers of employee retention, few studies have examined how these factors influence loyalty through job satisfaction in the context of five-star hotels. This study aims to analyze the effects of career development and employee engagement on employee loyalty, with job satisfaction acting as a mediating variable. Using a quantitative approach, data were collected from employees working in five-star hotels in Greater Jakarta between January and March 2025 and analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal significant positive relationships among variables. Employee engagement exerts a strong influence on job satisfaction (β = 0.468), which, in turn, enhances employee loyalty (β = 0.444). In contrast, career development shows the weakest direct effect on loyalty (β = 0.153), indicating that emotional engagement and daily work experiences play a more prominent role in shaping employee commitment than long-term career advancement opportunities. Furthermore, job satisfaction is confirmed as a mediating mechanism that translates organizational investments in career development and employee engagement into sustained employee loyalty. These findings contribute to hospitality management literature by emphasizing the central role of psychological and emotional engagement in strengthening employee loyalty. From a practical perspective, hotel management should prioritize strategies that foster employee engagement, recognition, and positive workplace experiences to enhance job satisfaction and build long-term employee commitment.